A secret about a secret - Spiegelman, Peter (Alfred A. Knopf, 2022)
"A Secret About a Secret is a gripping new mystery about a shadowy government agent investigating a bizarre murder in an ominous research facility. Myles, an agent with the powerful and mysterious government agency Standard Division, is sent to investigate the murder of Allegra, a brilliant young researcher, whose body is found in the walk-in refrigerator of the remote campus for Ondstrand Biologic. Cunning, persistent, and willing to lean on the authority of his badge, Myles begins to unravel the sequence of events that led to her death and narrow down the list of suspects. But the deeper he gets into the investigation, the more he feels that he's not getting the full picture. What interest does Standard Division, an organization better known for intelligence gathering and dirty tricks, have in this particular case? Why did Ondstrand Biologic pick an unmistakably eerie former boarding school for its headquarters? And how do recent events relate to the troubled history of this location? As Myles learns more about Allegra and the company she worked for, the more he is convinced that the murder is but one element in a much deeper mystery. In order to unlock it, he will have to put the pieces together to uncover the truth behind this peculiar place and the reason for Allegra's untimely death"--